2018
DOI: 10.2478/vzoo-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes of the Genus Trichuris (Nematoda, Trichuridae), Parasitizing Sheep in Central and South-Eastern Regions of Ukraine

Abstract: Nematodes of the GenusТrichuris (Nematoda, Trichuridae) Parasitizing Sheep in Central and South-Eastern Regions of Ukraine. Yevstafi eva, V. A., Yuskiv, I. D., Melnychuk, V. V., Yasnolob, I. O., Kovalenko, V. A., Horb, K. O. -Abundance and distribution of nematodes of the genus Тrichuris Schrank, 1788 parasitizing domestic sheep (Ovis aries Linnaeus, 1758) were studied in Poltava, Kyiv and Zaporizhzhia Regions of Ukraine. Th ree species of Тrichuris were found, Trichuris skrjabini Baskakov, 1924, Trichuris оvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…Some of the pioneering studies of Trichuris species identification stated the fact that body length and body spicules were the most reliable characteristics for differentiation among the species [18,41]. Likewise, pericloacal papillae were considered to be useful criteria for species distinction by other researchers [42]. Though, still some of the species of this genus were challenging to identify based on these criteria [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the pioneering studies of Trichuris species identification stated the fact that body length and body spicules were the most reliable characteristics for differentiation among the species [18,41]. Likewise, pericloacal papillae were considered to be useful criteria for species distinction by other researchers [42]. Though, still some of the species of this genus were challenging to identify based on these criteria [13].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of nematodes of the genus Trichuris spp. among sheep in the central and south-eastern regions of Ukraine was 65.9% (Yevstafieva et al, 2018). Three species of Trichuris were found, T. skrjabini Baskakov, 1924, T. ovis Abildgaard, 1795and T. globulosa Linstow, 1901.…”
Section: Discussionmentioning
confidence: 98%
“…Further research on sheep reported a variable prevalence of 6.25% (using faecal flotation) and 27.42% (using morphology of adults) [16]. Recently, Yevstafieva et al [17] reported 65% of sheep were infected with Trichuris spp. using morphological techniques.…”
Section: Trichuris In Deer Located In the Neo-tropicsmentioning
confidence: 99%